공사관리를 위한 고속도로 BIM 산출물의 표준 지침서 적용 및 개선 방안 도출 - 김한도; 남정용; Kim, Hando; Nam, Jeongyong (한국건설관리학회 논문집, 26(2), 2025)
Recently, MOLIT (Ministry of Land, Infrastructure and Transport) announced the BIM guidelines such as basic guideline and implementation guideline with a higher hierarchy, and then employers published the application guidelines with a lower hierarchy. This established a hierarchical system for BIM work procedures that proceeds from basics, implementation, application, and work manual. Among these, the Korea Expressway Corporation's BIM application guideline describes detailed procedures such as the composition of BIM data (WBS, OBS, CBS, etc.) of expressways, quality inspection, and submission system. The expressway project BIM results were applied to application guideline in order to derive implications. The tested BIM results did not include BIM data, and the modeling object division did not meet the WBS criteria, and the accuracy was low because there were no modeling regulations for auxiliary facilities. Therefore, new BIM data was constructed to apply the guideline correctly, and the data integrity was confirmed through quality inspection, and a web-based 5D project management system was finally implemented. Among BIM data modeling, the most difficult task is the WBS-CBS configuration work, which requires training of specialized civil expert, and it is concluded that a unified national data framework for the same structure (e.g. bridge) regardless of facilities should be established through consultation group between employers. 최근 국토교통부에서는 상위 지침인 BIM 기본지침 및 시행지침을 발표하였고, LH나 한국도로공사 등 발주처에서 하위 위계를 갖는 적용지침을 발간하였다. 이로써 BIM 업무 절차에 대해 기본, 시행, 적용 및 실무요령으로 이어지는 체계가 정립되었다. 이 중 한국도로공사의 BIM 적용지침은 고속도로의 BIM 데이터(WBS, OBS, CBS, Pset, Qset 등) 구성, 품질검수, 납품절차 및 체계 등의 상세한 절차를 기술하고 있으며, 최근 고속도로 프로젝트 BIM 산출물을 이에 적용하여 시사점을 도출하였다. 그 결과, 검증한 산출물에는 BIM 데이터가 포함되지 않았고, 모델링 객체 분할이 WBS 기준에 부합하지 않거나 부대시설의 모델링 규정이 없어 정밀도가 낮았다. 따라서 올바른 지침 적용을 위해 새로 BIM 데이터를 구축하였고 품질 검수를 통해 데이터 무결성을 확인하여 최종적으로 웹기반 5D 공사관리시스템을 구현하였다. BIM 데이터 모델링 중에서 가장 난이도가 높은 WBS-CBS 구축작업에는 전문인력 양성이 필요하며, 지침적용의 확산을 위해 정기적인 교육이 필요하고, 대부분의 항목에서 BIM 산출물에 대해 자동으로 품질검수가 되는 체계를 확립하고, 발주처간 상시 협의를 통해 시설물에 상관없이 동일한 구조물(예를 들어 교량)의 범국가적인 통일된 데이터 구조를 정립해야 할 것으로 사료된다.